MW‐assisted hydrothermal liquefaction of spent coffee grounds. (24th August 2021) - Yang, Jie; Niu, Haibo; Corscadden, Kenneth; He, Quan; Zhou, Ningning
Abstract: Hydrothermal liquefaction (HTL) is an attractive technology to process biomass to biocrude and hydrochar, and most studies have been using batch, tube, or continuous reactors with conventional heating. Attempts on microwave (MW)‐assisted HTL (MW‐HTL) is limited, and the effect of the heating rate on product distribution remains unexplored. There is also a lack of information on the MW effect in HTL processes. This study focused on the HTL of spent coffee grounds (SCG, most of which are currently disposed of in landfills) under MW irradiation. The investigation on the effect of heating rate revealed that increasing heating rate from 4.5 to 13.5°C/min promoted the biocrude formation and reduced the amount of solid residue. A low feedstock concentration of 8.3 wt.% was favourable for MW‐HTL of SCG compared to 14.3 wt.%. At a reaction temperature of 270°C, the biocrude yield gradually increased from 20.9 to 30.1 wt.% in response to an increase in reaction time from 0 to 20 min. In terms of the quality of products derived from MW‐HTL, the biocrude exhibited a satisfactory higher heating value (31.3 MJ/kg), and the solid residue, hydrochar, had a high specific surface area of 247.5 m 2 /g. As for the MW effect, MW and conventional heating resulted in comparable biocrude yield (27.8 vs. 25.7 wt.%, respectively). The characterization of biocrude, hydrochar, and aqueous phase also suggested that MW irradiation had no significant promotion effect on HTL under the experimental conditions in the study. Abstract : MW‐assisted hydrothermal liquefaction.